Aminocatalytic Enantioselective Cycloadditions - Vicario, Jose L. (Synlett, 2016)
Aminocatalysis applied to cycloaddition chemistry has gained an outstanding level of efficiency and sophistication, with many examples in which the different organocatalytic activation manifolds have been applied to develop catalytic and enantioselective variants of synthetically relevant cycloaddition reactions. In this account, a selection of relevant contributions to this field carried out in our laboratories will be presented, showing that the catalytic generation of either electron-poor α,β-unsaturated iminium ions or, alternatively, electron-rich dienamines or trienamines can constitute a very useful approach for the activation of (poly)unsaturated aldehydes toward different types of reagents. Importantly, this account also shows that reactions can be designed from the beginning leading to the expected products and that proceed with excellent performance once an appropriate catalyst and conditions are selected. Alternatively, it is also shown that, in some cases, unexpected results are obtained which have led us to the discovery of interesting transformations that are unprecedented in the chemical literature.1 Introduction2 Formal [3+2] Cycloaddition with Azomethine Ylides3 Attempted [3+2] Cycloaddition Using Hydrazones as Azomethine Imine Precursors4 [5+2] Cycloaddition Between Oxidopyrylium Ylides and Enals under Dienamine Activation5 [2+2] Cycloaddition Between Nitroalkenes and Enals under Dienamine Activation6 Trienamine Activation. Unconjugated Dienals as Active Substrates in [4+2] Cycloaddition7 Summary and Outlook
Keywords: asymmetric catalysis; cycloaddition; heterocycles; organocatalysis; ylides